A proteomic profiling of laser‐microdissected lung adenocarcinoma cells of early lepidic‐types - Yasufumi Kato; Haruhiko Nakamura; Hiromasa Tojo; Masaharu Nomura; Toshitaka Nagao; Takeshi Kawamura; Tatsuhiko Kodama; Tatsuo Ohira; Norihiko Ikeda; Thomas Fehniger; György Marko‐Varga; Toshihide Nishimura; et al. (Clinical and Translational Medicine, 2015)
Abstract BackgroundIn the new pathologic classification of lung adenocarcinoma proposed by IASLC/ATS/ERS in 2011, lepidic type adenocarcinomas are constituted by three subtypes; adenocarcinoma in situ (AIS), minimally invasive adenocarcinoma (MIA) and lepidic predominant invasive adenocarcinoma (LPIA). Although these subtypes are speculated to show sequential progression from preinvasive lesion to invasive lung cancer, changes of protein expressions during these processes have not been fully studied yet. This study aims to glimpse a proteomic view of the early lepidic type lung adenocarcinomas. MethodsA total of nine formalin‐fixed and paraffin‐embedded (FFPE) lepidic type lung adenocarcinoma tissues were selected from our archives, three tissues each in AIS, MIA and LPIA. The tumor and peripheral non‐tumor cells in these FFPE tissues were collected with laser microdissection (LMD). Using liquid chromatography‐tandem mass spectrometry (MS/MS), protein compositions were compared with respect to the peptide separation profiles among tumors collected from three types of tissues, AIS, MIA and LPIA. Proteins identified were semi‐quantified by spectral counting‐based or identification‐based approach, and statistical evaluation was performed by pairwise G‐tests. ResultsA total of 840 proteins were identified. Spectral counting‐based semi‐quantitative comparisons of all identified proteins through AIS to LPIA have revealed that the protein expression profile of LPIA was significantly differentiated from other subtypes. 70 proteins including HPX, CTTN, CDH1, EGFR, MUC1 were found as LPIA‐type marker candidates, 15 protein candidates for MIA‐type marker included CRABP2, LMO7, and RNPEP, and 26 protein candidates for AIS‐type marker included LTA4H and SOD2. The STRING gene set enrichment resulted from the protein‐protein interaction (PPI) network analysis suggested that AIS was rather associated with pathways of focal adhesion, adherens junction, tight junction, that MIA had a strong association predominantly with pathways of proteoglycans in cancer and with PI3K‐Akt. In contrast, LPIA was associated broadly with numerous tumor‐progression pathways including ErbB, Ras, Rap1 and HIF‐1 signalings. ConclusionsThe proteomic profiles obtained in this study demonstrated the technical feasibility to elucidate protein candidates differentially expressed in FFPE tissues of LPIA. Our results may provide candidates of disease‐oriented proteins which may be related to mechanisms of the early‐stage progression of lung adenocarcinoma.